Taxonomic status of maskrays of the Neotrygon kuhlii species complex (Myliobatoidei: Dasyatidae) with the description of three new species from the Indo-West Pacific - Last, Peter R.; White, William T.; Séret, Bernard (Zootaxa, 2016)
The bluespotted maskray, Neotrygon kuhlii (Müller & Henle, 1841), once thought to be widely distributed in the Indo-West Pacific, consists of a complex of several species and the type series consists of multiple species; its nomenclature is discussed. A lectotype and paralectotype are designated and the species rediagnosed based on the types and a fresh specimen from Honiara (Solomon Islands), near to the collection locality of the lectotype (Vanikoro, Solomon Islands). Molecular and morphological data provide confirmatory evidence that this maskray is distinct from some other regional forms. Three members of the complex from the Western Pacific identified in earlier studies are confirmed to be new species; Neotrygon australiae sp. nov. (Australia, New Guinea and eastern Indonesia), N. caeruleopunctata sp. nov. (Indian Ocean), and N. orientale sp. nov. (North-West Pacific). These species differ from each other and N. kuhlii in their adult size, anterior angle of the disc, number and distribution of blue spots on the dorsal disc, and other more subtle morphometric and meristic characters. Another largely plain-coloured Neotrygon, also currently misidentified as N. kuhlii, is sympatric with N. orientale sp. nov. in the South China Sea and off Taiwan. Neotrygon varidens (Garman) is resurrected as the valid name for this ray. A key is provided to species of the genus.